Амет ва Айимхан Шамуратовалар уй-музейи тарихи - Хужаниязов, У (SCIENCE and SOCIETY, 2024)
This article describes the history of the house-museum of Amet and Ayimkhan Shamuratov, created in the city of
Keywords: independence; law; house-museum; hall; tourists; museum culture; museum fund; works of art; literature; cultural heritage